2018
DOI: 10.1111/cea.13245
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD14 concentration in human breast milk and its potential role in child atopic dermatitis: Results of the Ulm Birth Cohort Studies

Abstract: Our results do not support an association between sCD14 concentration in mature breast milk and AD among breastfed children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Previous studies have indicated that orally ingested sCD14 is considered the primary pattern recognition receptor of LPS specific to gram‐negative bacteria in the gastrointestinal tract . Moreover, it has been implicated in the development of resistance to potentially harmful bacteria and influences immune response programming . However, the association between sCD14 and atopic diseases remains unclear in clinical studies .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have indicated that orally ingested sCD14 is considered the primary pattern recognition receptor of LPS specific to gram‐negative bacteria in the gastrointestinal tract . Moreover, it has been implicated in the development of resistance to potentially harmful bacteria and influences immune response programming . However, the association between sCD14 and atopic diseases remains unclear in clinical studies .…”
Section: Discussionsupporting
confidence: 93%
“…As the sCD14 level in the colostrum is significantly higher than that in the mature milk (Figure 1), we proposed that higher sCD14 concentrations in early infancy, rather than longer duration of breastfeeding, may be a more important factor that influences the development of an infant's immune system, gut microbiome, and possible atopic outcomes later in life. 20 Inconsistent results obtained from other studies regarding the associations between sCD14 and allergic manifestations 5,23,24 may be related to varying HM collection periods (from colostrum to 3-month HM), differences in atopy classification methods (eg, parent or physician's report), wide range of assessed atopic outcomes (eg, atopic dermatitis, wheeze, or asthma), and varying follow-up periods (from 1 to 5 years).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although 1 study found maternal linkage on a locus associated with AD, 209 no studies have found evidence of paternal imprinting in AD, [210][211][212] and no clear mediating pathways have been established related to IgE, 51,58,114,136,173,[213][214][215] inflammatory cytokines, 28,173,213,[216][217][218][219][220] and cellular immunity 104,[221][222][223] measured in cord blood or breast milk composition. [224][225][226][227] Consequently, the hypothesis of preferential maternal inheritance in AD remains unsupported by robust biological models, and we observed a comparable effect of maternal and paternal inheritance.…”
Section: Comparison With Other Studiesmentioning
confidence: 54%
“…By contrast, Savilahi et al documented that higher sCD14 levels in BM 3 months postpartum were associated with IgE-mediated allergic disorders by the age of 5 years [22]. Other studies found sCD14 levels either in colostrum or mature milk were not associated with subsequent development of eczema or atopic sensitization during early life [23,24,25,26]. The substantial variations in study protocols, such as time of outcome measurement, selection of subjects, change in other immunomodulators in BM with time, etc., may contribute to these conflicting results.…”
Section: Introductionmentioning
confidence: 99%